Bohemian Bolsheviks After World War II: A Minority within a Minority - Wald, Alan (Labour / Le Travail, 2012)
Institutionalized forgetting about the scope of the Trotskyist experience in the United States was on display in every venue following the deaths of Peter Rafael Bloch (1921-2008), an authority on Puerto Rican artistic culture, and George Perle (born George Perlman, 1915-2009), a Pulitzer Prize-winning music theorist and composer once married to the sculptress and painter Laura Slobe (1909-58). Nothing written even hinted that the two iconoclasts were in the past highly educated and committed Marxists, or that revolutionary ideas oxygenated their cultural thinking at crucial moments. Alarm over memory loss of this type is the motive for this present essay, which appraises the lives of Bloch, Perle, and Slobe along with other "Bohemians" who sought a vexed amalgam of unconstrained cultural creativity, personal freedom, and disciplined "Bolshevik" politics in the Socialist Workers Party (swp) during the late 1940s and 1950s. What can be recovered of the political and personal passions of many "outlaw" lives on the Left, of cultural revolutionaries and sexual non-conformists, especially from those who infused anti-capitalism with anti-Stalinism, are only fragmentary narratives to be steered warily into coherency. For the postwar decade, one must write a kind of ghostly history, the reconstruction of the presence of an absence in a time of persecution.
Keywords: BLOCH, Peter Rafael; BOHEMIANISM -- United States; BOLSHEVISM; COMMUNISTS -- United States; PERLE, George; Social aspects; TROTSKYISM; United States

The Cultural Front: The Laboring of American Culture in the Twentieth Century - Wald, Alan (Labour / Le Travail, 1998)
The article reviews the book, "The Cultural Front: The Laboring of American Culture in the Twentieth Century," by Michael Denning.

"A Seemingly Incongruous Alliance": Trotskylsts and Teamsters in 1934 - Wald, Alan (Labour / Le Travail, 2014)
The article reviews and comments extensively on the book, "Revolutionary Teamsters: The Minneapolis Teamsters Strikes of 1934," by Bryan D. Palmer.
Keywords: History; INTERNATIONAL Brotherhood of Teamsters; MINNEAPOLIS (Minn.); Nonfiction; PALMER, Bryan D.; REVOLUTIONARY Teamsters: The Minneapolis Truckers' Strikes of 1934 (Book)

Marxism in the United States: From 1870 to the Present Day - Wald, Alan (Labour / Le Travail, 1989)
The article reviews the book, "Marxism in the United States: From 1870 to the Present Day," by Paul Buhle.
Keywords: BUHLE, Paul; Communism; MARXISM in the United States: From 1870 to the Present Day (Book); Nonfiction; REVIEWS; books